2009
DOI: 10.1016/j.hitech.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Competing explanations for knowledge exchange: Technology sharing within the globally dispersed R&D of the multinational enterprise

Abstract: This paper explores five competing theories for technological knowledge sharing within the globally dispersed R&D function of the multidivisional, multinational firm. These five broad explanations for why a knowledge transaction occurs are: (1) economic, (2) technological, (3) organizational, (4) geographic, and (5) sociological. In addition to occurrence, likelihood of knowledge exchange success prompted by various explanations is considered. Ultimately the determination of which argument-or combination of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…From a theoretical standpoint, we support Batifoulier and Larquier (), who recognized the suitability of convention theories to diagnose or explain concrete problems faced by organizations. Our findings also provide empirical support for claims made by Ensign and Hébert () about the need for research that will reconcile various perspectives. Through hybridization and consideration of the various logics research can provide empirical findings that are relevant for practice.…”
Section: Theoretical and Managerial Implicationssupporting
confidence: 83%
See 1 more Smart Citation
“…From a theoretical standpoint, we support Batifoulier and Larquier (), who recognized the suitability of convention theories to diagnose or explain concrete problems faced by organizations. Our findings also provide empirical support for claims made by Ensign and Hébert () about the need for research that will reconcile various perspectives. Through hybridization and consideration of the various logics research can provide empirical findings that are relevant for practice.…”
Section: Theoretical and Managerial Implicationssupporting
confidence: 83%
“…Ensign and Hébert () explored five competing ideas to explain why technological knowledge‐sharing occurred within the globally dispersed R&D function of the multidivisional, multinational firm. These explanations were: (1) economic, (2) technological, (3) organizational, (4) geographic and (5) sociological.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As we discussed above, obtaining external knowledge across international boundaries is not straightforward, and prior studies of knowledge exchange at individual level (Allen 1990;Ensign and Hébert 2009; have found that social relationships of individuals affect knowledge diffusion. This literature has suggested that knowledge receivers and knowledge senders need to share a common ground and understand the social and cultural context in which knowledge is developed (Buckley et al, 2005;Harzing, et al, 2011).…”
Section: Returnees and The Effectiveness Of Reverse Knowledge Spilloversmentioning
confidence: 98%
“…Projects of collaborative research category relatively pro duce outputs could be clearly measured by academic achievements of papers, patents, rewards and so on. Never theless, perceived output of exchange category is more fo cused on the intangible aspect [12], such as communication, researchers training and increased awareness of R&D.…”
Section: E Fr Amework Of Performance Evaluationmentioning
confidence: 99%